Strengths and Limitations of Conventional Approaches to the Risk Assessment and Management of EMF Exposure From 5G and B5G Networks - Mazar, Haim; Ball, David J. (Frontiers in Communications and Networks, 2021)
This paper describes the current science-based approach to ensuring public safety from RF-EMF base stations. It acknowledges that a degree of public concern persists despite the fact that dose limits are seldom if ever approached in practice. One plausible contributor to the discord is a tendency within parts of academia and by some planning authorities to pursue a technocratic policy approach to siting wherein public concerns are attributed to scientific uncertainty over health risks, whereas the reality is that societal concerns over base stations is broader. Thus, potential mis-framing of the debate as a purely scientific issue leads to inappropriate risk communication exercises which in fact polarise the situation by disenfranchising other potentially legitimate siting concerns. It is recommended that more attention should be paid to the non-health related siting issues, which could be handled by a thoughtful democratic / deliberative process, and that this should not be conflated with the scientific debate over the uncertain and possibly non-existent risks posed by RF EMF complying with the existing science-based dose limits.